Substance use disorder in the anaesthetist: Guidelines from the Association of Anaesthetists. (21st April 2022) - Misra, U.; Gilvarry, E.; Marshall, J.; Hall, R.; McLure, H.; Mayall, R.; El‐Ghazali, S.; Redfern, N.; McGrady, E.; Gerada, C.
Summary: Anaesthetists have a higher incidence of substance use disorder when compared with other doctors. This might be due to the ease of access to intravenous opioids, propofol, midazolam, inhalational agents and other anaesthetic drugs. Alcohol use disorder continues to be the most common problem. Unfortunately, the first sign that something is amiss might be the anaesthetist's death from an accidental or deliberate overdose. While there are few accurate data, suicide is presumed to be the cause of death in approximately 6–10% of all anaesthetists. If we are to prevent this, substance use disorder must be recognised early, we should ensure the anaesthetist is supported by their department and hospital management and that the anaesthetist engages fully with treatment. Over 75% of anaesthetists return to full practice if they co‐operate fully with the required treatment and supervision.